Multicast-Based Mobile Ipv6 Join/Leave Mechanism Software - A.M. Ali, Sahar (2003)
Increasing demand for mobility in the Internet has created the need for a routing protocol that allows a host to roam in the network. Mobile IP is a solution that enables an IP host to leave its home link while transparently maintaining all of its present connections and remaining reachable to the rest of the Internet. The Internet Engineering Task Force (IETF) has standardized Mobile IPv4. Mobile IPv6 is a work in progress in the IETF, offering support for IPv6 mobile nodes. Although it is not yet standardized, every IPv6 node is required to implement Mobile IPv6, which means that mobility must be widely supported. IP-multicast provides efficient algorithms for multiple packet delivery. It also provides location-independent group addressing. The receiver-initiated approach for IP-multicast enables new receivers to join to a nearby branch of an already established multicast tree. Hence, IP-multicast provides a scalable infrastructure for efficient, location-independent, packet delivery.The recent advances in wireless communication technology and the growth of the Internet have paved the way for wireless networking and IP mobility. Unlike conventional wired networks, wireless networks possess different channel characteristics and mobility dynamics that render network design and analysis more cha1lenging. Performance during handoff where the mobile moves from one cell, or coverage area, to another is a significant factor in evaluating wireless networks.